2017
DOI: 10.1002/jcb.26243
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Effects of astragalus polysaccharide on apoptosis of myocardial microvascular endothelial cells in rats undergoing hypoxia/reoxygenation by mediation of the PI3K/Akt/eNOS signaling pathway

Abstract: The study explores the effect of astragalus polysaccharide (APS) mediating P13K/ Akt/eNOS signaling pathway on apoptosis of myocardial microvascular endothelial cells (MMECs) in hypoxia/reoxygenation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…PI3K/Akt signaling is shown to play a protective role in myocardial ischemia-reperfusion. [17][18][19] Interestingly, a recent study reported that Notch signaling acted upstream of Akt to mediate the protective effects of oncostatin M on myocardial ischemia/reperfusion injury. 20 In addition, our previous study showed that Hes1 downregulated the expression of PTEN and promoted the phosphorylation of Akt in cardiac myocytes exposed to H/R, leading to improved cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/Akt signaling is shown to play a protective role in myocardial ischemia-reperfusion. [17][18][19] Interestingly, a recent study reported that Notch signaling acted upstream of Akt to mediate the protective effects of oncostatin M on myocardial ischemia/reperfusion injury. 20 In addition, our previous study showed that Hes1 downregulated the expression of PTEN and promoted the phosphorylation of Akt in cardiac myocytes exposed to H/R, leading to improved cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…The results from the present study supported this finding and clarified that pretreatment with XNJ reduced these changes in rat cerebral tissue. Endothelial NO synthase (eNOS) has been proved to play a critical role in proliferation and apoptosis by suppressing the proapoptotic proteins [ 27 , 28 ]. NO produced by eNOS is considered to be a protective event against brain I/R injury [ 29 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…H/R is an accepted and ideal in vitro model mimicking I/R injury [ 21 ]. It was reported that endothelial cells are very vulnerable to I/R and H/R injury [ 7 , 22 ]. In the present study, we found that H/R exposure significantly induced apoptosis of cultured HAECs, resulting in the dramatic inhibition of cell viability.…”
Section: Discussionmentioning
confidence: 99%